Tourist Perception of Mangrove Ecotourism Development in Tuada Village, West Halmahera Regency - Boga, Saul; Niapele, Sabaria; Salim, Tamrin (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The purpose of this study is to find out the perception of tourists towards the development of mangrove ecotourism in Tuada village in West Halmahera Regency. The research was carried out from November 2023 to January 2024. The method in this study uses a qualitative descriptive approach. The number of respondents was 75 people. The data in this study includes primary data and secondary data. Based on the results of research that has been carried out on the mangrove tourism area in Tuada village, it can be concluded that: The perception of tourists in general supports and wants the development of mangrove forest tourism in Tuada Village as an ecotourism area by providing suggestions in its management as follows: The road accessibility aspect needs to be improved in the condition of damaged and potholed roads, (b) The aspect of infrastructure facilities needs to be added and arranged according to ecotourism activities, (c) The aspect of tourist objects and attractions needs to be maintained in the panorama of the mangrove forest, (d) The management aspect needs to have tour guides and also tourism promotion that needs to be improved